ANALISIS IKON DAN INDEKS DALAM SEMIOTIKA CHARLES SANDERS PIERCE PADA FILM DOKUMENTER “KAWALI, IDENTITAS LAKI-LAKI BUGIS” - Saifullah, Saifullah; Asrullah, Asrullah; Asrifan, Andi; Zain, Suardi; Yusmah, Yusmah; Rasyid, Rustam (UNIB Press, 2021)
This study aims to describe Icons and Indexes in Charles Sanders Peirce's semiotics in the documentary film “Kawal, Bugis Male Identity”. This study uses the theory of Charles Sanders Peirce which is often referred to as the